Secondary respiratory early and late infections in mechanically ventilated patients with COVID-19 - María Elena Ceballos; Carolina Nuñez; Javier Uribe; María Magdalena Vera; Ricardo Castro; Patricia García; Gabriel Arriata; Vicente Gándara; Camila Vargas; Angélica Dominguez; Inés Cerón; Pablo Born; et al. (BMC Infectious Diseases, 2022)
Abstract Background Patients with COVID-19 receiving mechanical ventilation may become aggravated with a secondary respiratory infection. The aim of this study was to describe secondary respiratory infections, their predictive factors, and outcomes in patients with COVID-19 requiring mechanical ventilation. Methods A cohort study was carried out in a single tertiary hospital in Santiago, Chile, from 1st June to 31st July 2020. All patients with COVID-19 admitted to the intensive care unit that required mechanical ventilation were included. Results A total of 175 patients were enrolled, of which 71 (40.6%) developed at least one secondary respiratory infection during follow-up. Early and late secondary infections were diagnosed in 1.7% and 31.4% respectively. Within late secondary infections, 88% were bacterial, 10% were fungal, and 2% were of viral origin. One-third of isolated bacteria were multidrug-resistant. Bivariate analysis showed that the history of corticosteroids used before admission and the use of dexamethasone during hospitalization were associated with a higher risk of secondary infections (p = 0.041 and p = 0.019 respectively). Multivariate analysis showed that for each additional day of mechanical ventilation, the risk of secondary infection increases 1.1 times (adOR = 1.07; 95% CI 1.02–1.13, p = 0.008) Conclusions Patients with COVID-19 admitted to the intensive care unit and requiring mechanical ventilation had a high rate of secondary infections during their hospital stay. The number of days on MV was a risk factor for acquiring secondary respiratory infections.